Clinical and Market Analysis of NanoBEO: A Public-Worth, Innovative Therapy for Behavioral and Psychological Symptoms of Dementia (BPSD)-Emerging Evidence and Its Implications for a Health Technology Assessment (HTA) and Decision-Making in National Health Systems - Damiana Scuteri; Daniele Pierobon; Martina Pagliaro; Kengo Hamamura; Takafumi Hayashi; Loris Pignolo; Pierluigi Nicotera; Giacinto Bagetta; Maria Tiziana Corasaniti (MDPI AG, 2024)
Background: According to scientific literature, some 99% of patients affected by Alzheimer's disease (AD) suffer from behavioral and psychological symptoms of dementia (BPSD), also known as neuropsychiatric symptoms (NPSs). In particular, agitation is one of the most difficult disorders to treat. States of agitation represent a very serious problem as they make these subjects dangerous for themselves and others and worsen as the disease advances. To date, there are no specific solutions for treating agitation. The only authorized drug is risperidone (as well as brexpiprazole, approved by the FDA on 11 May 2023), which can be used for no longer than 6-12 weeks because it increases the risk of death-owing to cardiocerebrovascular accidents-by 1.6-1.7 times. Methods: In order to address the latter noteworthy unmet medical need, NanoBEO was produced. The aim of the present work is to generate the health technology assessment (HTA) of this nanotechnological device. The latter consists of a controlled release system, based on solid lipid nanoparticles loaded with bergamot essential oil (BEO). Results: The results of the present research assessed the current evidence in the field of non-pharmacological treatments for this condition, including relevant primary preclinical and clinical data studies supporting the use of this device and the production of the operative plan for its launch on the market. The findings offer recommendations for decision-making on its implementation in dementia. Conclusions: NanoBEO represents a public-worth innovation in this neglected area, marking a significant advancement in the history of dementia, moving from academic research to product development.